1982
DOI: 10.1172/jci110517
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Glucose Metabolism following Exercise in the Rat

Abstract: A B S T R A C T Muscle glycogen stores are depleted during exercise and are rapidly repleted during the recovery period. To investigate the mechanism for this phenomenon, untrained male rats were run for 45 min on a motor-driven treadmill and the ability of their muscles to utilize glucose was then assessed during perfusion of their isolated hindquarters. Glucose utilization by the hindquarter was the same in exercised and control rats perfused in the absence of added insulin; however, when insulin (30-40,000 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
290
2
3

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 458 publications
(312 citation statements)
references
References 35 publications
17
290
2
3
Order By: Relevance
“…This is consistent with previous reports of increased whole body or skeletal muscle insulin sensitivity persisting for 4 -48 h after a single bout of exercise in humans (34,46,54) and 4 -48 h after acute exercise in rodents (8,18,44). This is the first report of exercise-induced increases in insulin sensitivity in a nonhuman large animal.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This is consistent with previous reports of increased whole body or skeletal muscle insulin sensitivity persisting for 4 -48 h after a single bout of exercise in humans (34,46,54) and 4 -48 h after acute exercise in rodents (8,18,44). This is the first report of exercise-induced increases in insulin sensitivity in a nonhuman large animal.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies in humans and rodents have reported increased insulin sensitivity after either higher-intensity or longer-duration acute exercise protocols than used in the present study (3,8,15,19,23,34,43,44,54). The exercise intensity achieved in the present study by sheep in the intensive exercise test (30 min, 8% slope, 4 -4.4 km/h) is probably ϳ50 -60% of V O 2max , based on studies in pregnant sheep (26).…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…Of note, exercise is associated with increased insulin-stimulated glucose uptake in the immediate postexercise period [2,3], while chronic physical activity enhances insulin sensitivity [4]. We have recently identified skeletal muscle as a cytokine-producing organ, demonstrating that the metabolic and physiological effects of exercise may also be mediated by skeletal muscle-derived humoral factors [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The insulinindependent effect is evident during and shortly after exercise, but it reverses relatively rapidly, with most of the effect typically lost ϳ3-4 h postexercise in rat muscle (10,43). As the exercise effect on insulin-independent glucose transport subsides, glucose transport in the presence of a physiological insulin concentration can be substantially elevated (9,10,32,43).…”
mentioning
confidence: 99%